2021
DOI: 10.3390/cancers13071685
|View full text |Cite
|
Sign up to set email alerts
|

RTK Inhibitors in Melanoma: From Bench to Bedside

Abstract: MAPK (mitogen activated protein kinase) and PI3K/AKT (Phosphatidylinositol-3-Kinase and Protein Kinase B) pathways play a key role in melanoma progression and metastasis that are regulated by receptor tyrosine kinases (RTKs). Although RTKs are mutated in a small percentage of melanomas, several receptors were found up regulated/altered in various stages of melanoma initiation, progression, or metastasis. Targeting RTKs remains a significant challenge in melanoma, due to their variable expression across differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 223 publications
(270 reference statements)
2
26
0
Order By: Relevance
“…The present study used B16BL6 and MEWO cells. Other studies have reported that B16 cell lines express wild-type B-Raf, and offer a model system for studying alternative mechanisms that give rise to malignant melanoma (43)(44)(45)(46). MeWo cells were also reported to express c-Kit (47).…”
Section: Discussionmentioning
confidence: 98%
“…The present study used B16BL6 and MEWO cells. Other studies have reported that B16 cell lines express wild-type B-Raf, and offer a model system for studying alternative mechanisms that give rise to malignant melanoma (43)(44)(45)(46). MeWo cells were also reported to express c-Kit (47).…”
Section: Discussionmentioning
confidence: 98%
“…There are already several different drugs that are available for the extraocular melanomas, such as BRAF inhibitors and c-KIT inhibitors, and it is possible repurpose them to treat CM [45][46][47]. These therapies are helping the management of melanomas, but they do not always induce remission.…”
Section: Discussionmentioning
confidence: 99%
“…Dubermatinib is another selective AXL inhibitor that was investigated in CLL (NCT03572634) and solid tumors (NCT02729298). Other non-selective AXL inhibitors that have the latter among their targets, such as crizotinib, bosutinib, and cabozantinib, and multi-targeted TKI, such as sunitinib, foretinib, and sitravatinib, are also available in clinics [ 126 ].…”
Section: Targeting Phenotypic Plasticity: Identifying New Vulnerabili...mentioning
confidence: 99%